Committing consumers to sustainability: Portugal and South Korea outlooks - Loureiro, S. M. C.; Bilro, R. G.; Koo, D.-M. (4th International Conference on Multinational Enterprises and Sustainable Development, (MESD'15), 2015)
The importance of recycling and environmental preservation has continued to receive increasing attention from governments, enterprises, and consumers. However, little research examines the factors that influence individuals’ commitment to recycling and environmental preservation, and even less explores how that commitment can lead to preferential behavior, word of mouth and willingness to sacrifice for recycling and environmental preservation. This study examines the roles of need for self-expression and arousal to explain commitment and whether commitment leads to those behaviors. The study is duplicated in two countries, each representing different cultural dimensions. Data collected from respondents in South Korea and Portugal inform a model that supports the majority of the hypotheses and points out some interesting differences in the ways that recycling and environmental preservation should be presented in various cultures to achieve buy-in.